Comparative Analysis of State-Owned Property Insurance Policies: A Study Between Indonesia and Other Countries - Pertiwi, Agnesti Shiffa; Nurbiyanto, nurbiyanto (Journal of Economics, Business, and Government Challenges, 2024)
This study aims to analyze the implementation of public asset insurance policies in the Philippines, New Zealand, and Australia and to evaluate how these policies can be adapted or applied in Indonesia. The research methods employed include literature review, interviews, and documentation. The results indicate that each country adopts different approaches tailored to their specific contexts and needs. The Philippines has the National Indemnity Insurance Program (NIIP) that provides comprehensive insurance protection for key government assets, New Zealand has the Local Authority Protection Programme (LAPP) designed to protect local government infrastructure, and Australia has Comcover, which offers insurance and risk management services for Australian government entities. The insurance policies in these three countries reflect national priorities and risk mitigation strategies, yet all aim to enhance the resilience and protection of public assets. The study finds that several elements of public asset insurance policies from the Philippines, New Zealand, and Australia can be adopted in Indonesia to improve the protection of state assets. For instance, the Philippines' flexibility in accessing the reinsurance market and adjusting insurance coverage, New Zealand's joint insurance program to protect national infrastructure, and Australia's efficiency in claims and comprehensive government equity protection. Adapting these elements in Indonesia is expected to enhance efficiency, coverage, and financial stability when facing various risks.